Exploring Tourists’ Booking Intention Through Brand Image, EWOM, and Experiential Marketing - Ni Luh Putu Indiani; Nyoman Yudhana; Ni Made Wahyuni (Department of Management, Faculty of Economics and Business, Brawijaya University, 2023)
Bali’s leading destination status leads to intense competition in the tourism industry, especially accommodation. This situation calls for a study that could provide marketing insight to accommodation business management on critical factors that shape tourists’ booking intention, as understanding the buyer’s decision behavior is one of the essential prerequisites of creating a successful marketing strategy. A survey was conducted to collect data. Respondents were prospective tourists who planned to book accommodation in Bali. The study received 167 valid samples. Data was analyzed using Partial Least Square. The results showed that eWOM and experiential marketing significantly affect brand image and booking intention. Brand image mediates the eWOM-booking intention relationship and experiential marketing-booking intention relationship. To encourage tourists’ booking intention, it is recommended to improve communication strategies through eWOM by encouraging tourists to share their experiences through electronic media and develop communication containing complete information. Brand image must also be strengthened by ensuring the hotel’s quality, attractiveness, and reputation.